Majas Pada Puisi Uhibuki Anti Karya Nader Haddad (Kajian Stilistika) - Sirait, Arbi Mulya (Ukazh : Journal of Arabic Studies, 2025)
This study aims to identify the types of figures of speech used in the poem "Uhibuki Anti" by Nader Haddad. By identifying the stylistic aspects of this poem, readers can understand how language can create beauty and emotional depth, so this poem is important to study. The method used in this study is qualitative, with a literature study approach. The main data source is the poem Uhibuki Anti itself, while secondary data sources are in the form of articles or writings relevant to the topic of discussion. The results of the study show that in the poem there are various types of figures of speech. First, the figure of speech comparison consisting of 4 figures of speech simile, 9 figures of speech personification, 1 figure of speech depersonification, 1 figure of speech synesthesia, and 1 figure of speech symbolic. Second, the figure of speech affirmation consisting of 8 figures of speech anaphora, 5 figures of speech mesodiplosis, and 1 figure of speech pleonasm. Third, the figures of speech of opposition consist of 1 litotes figure of speech and 3 apostrophes figures of speech. This research provides a new picture regarding the use of figures of speech in poetry, as well as providing an understanding of how contemporary figures of speech reflect new sensibilities (modern romance, identity), which differ from the conventions of classical poetry.